Highly enantioselective construction of tertiary thioethers and alcohols via phosphine-catalyzed asymmetric γ-addition reactions of 5H-thiazol-4-ones and 5H-oxazol-4-ones: scope and mechanistic understandings1. Issue 8 (14th August 2015) - Wang, Tianli; Yu, Zhaoyuan; Hoon, Ding Long; Huang, Kuo-Wei; Lan, Yu; Lu, Yixin
<x xml:space="preserve">Abstract</x> A new method for facile access to enantioenriched tertiary thioethers/alcohols.